Experimental study of a membrane-based dehumidification cooling system - Chen, Ziwei; Bai, Hongyu; Ye, Zihao; Zhu, Jie (2016)
Membrane-based liquid desiccant dehumidification has attracted increasing interests with elimination of solution droplets carryover problem. A membrane-based hybrid liquid desiccant dehumidification cooling system is developed in this study, which has the ability to remove latent load by a liquid desiccant dehumidification unit and simultaneously to handle sensible load by an evaporative cooling unit. The hybrid system mainly consists of a dehumidifier, a regenerator and an evaporative cooler, calcium chloride is used as liquid desiccant in the system. This paper presents a performance evaluation study of the hybrid system based on experimental data. Series of tests have been conducted to clarify the influences of operating variables and conditions (i.e. desiccant solution concentration ratio, regeneration temperature, inlet air condition, etc.) on the system performance. The experimental results indicate that the system is viable for dehumidification cooling purpose, with which the supply air is provided at temperature of 20.4°C for the inlet air condition at temperature of 34°C and relative humidity of 73%. At desiccant solution concentration ratio of 36%, the thermal COPth of 0.70 and electrical COPel of 2.62 are achieved respectively under steady operating condition.